The gap between medical and monetary choices under risk persists in decisions for others. (12th February 2019) - Popovic, Nathalie F.; Pachur, Thorsten; Gaissmaier, Wolfgang
Abstract: Decisions under risk in the medical domain have been found to systematically diverge from decisions in the monetary domain. When making choices between monetary options, people commonly rely on a decision strategy that trades off outcomes with their probabilities; when making choices between medical options, people tend to neglect probability information. In two experimental studies, we tested to what extent differences between medical and monetary decisions also emerge when the decision outcomes affect another person. Using a risky choice paradigm for medical and monetary decisions, we compared hypothetical decisions that participants made for themselves to decisions for a socially distant other (Study 1) and to recommendations as financial advisor or doctor (Study 2). In addition, we examined people's information search in a condition in which information about payoff distributions had to be learned from experiential sampling. Formal modeling and analyses of search behavior revealed a similarly pronounced gap between medical and monetary decisions in decisions for others as in decisions for oneself. Our results suggest that when making medical decisions, people try to avoid the worst outcome while neglecting its probability—even when the outcomes affect others rather than themselves.